Synergistic effects of rhizosphere effect and combined organic and chemical fertilizers application on soil bacterial diversity and community structure in oilseed rape cultivation - Wang, Jingyuan; Qin, Hongling; Zhang, Leyan; Tang, Yafang; Long, Junjiang; Xu, Huaqin; Zhu, Baoli (Frontiers in Microbiology, 2024)
The combined application of chemical and organic fertilizers has been recognized to enhance soil fertility and foster the soil microbial ecosystem. However, the optimal ratio of chemical and organic fertilizers in oilseed rape cultivation is still uncertain, and the role of rhizosphere effect is still unclear. Thus, this study aimed to elucidate the impacts of varying ratios of chemical and organic fertilizers on the structure and potential functionalities of rhizosphere and non-rhizosphere soil microbial communities. The interplay of microbial communities with soil properties and oilseed rape root exudates was investigated in controlled pot cultivations receiving varying ratios of chemical and organic fertilizers. Results indicated clear segregation in the soil bacterial community, influenced by both fertilization treatments and rhizosphere effects. The bacterial community structure significantly correlated with nitrate nitrogen, organic acids, and dissolved organic carbon (DOC) content. Rhizosphere effects led to increased bacteria abundance, reduced diversity, and decreased network stability. Notably, F3 treatment receiving 25% chemical and 75% organic fertilizers showed a significantly higher abundance at 1.43 × 1011 copies g−1 dry soil, accompanied by increased species and genetic diversity, and ecological network complexity. This treatment also yielded the highest aboveground biomass of oilseed rape. However, the application of organic fertilizers also increased the risk of plant pathogenicity. This study reveals the impact of fertilizers and rhizosphere effects on soil microbial community structure and function, shedding light on the establishment of more effective fertilization schemes for oilseed rape agriculture.